2008
DOI: 10.1016/j.smrv.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

From wakefulness to excessive sleepiness: What we know and still need to know

Abstract: The epidemiological study of hypersomnia symptoms is still in its infancy; most epidemiological surveys on this topic were published in the last decade. More than two dozen representative community studies can be found. These studies assessed two aspects of hypersomnia: excessive quantity of sleep and sleep propensity during wakefulness excessive daytime sleepiness. The prevalence of excessive quantity of sleep when referring to the subjective evaluation of sleep duration is around 4% of the population. Excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
126
4
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(142 citation statements)
references
References 48 publications
4
126
4
8
Order By: Relevance
“…Despite its high prevalence in both community and clinical populations (Ohayon, 2008;Rohers, Carskadon, Dement, & Roth, 2011), no clear consensus exists as to what constitutes sleepiness (Shen et al, 2006;Young, 2004). Traditionally, it has been considered as the physiological tendency to fall asleep (i.e., sleep propensity).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high prevalence in both community and clinical populations (Ohayon, 2008;Rohers, Carskadon, Dement, & Roth, 2011), no clear consensus exists as to what constitutes sleepiness (Shen et al, 2006;Young, 2004). Traditionally, it has been considered as the physiological tendency to fall asleep (i.e., sleep propensity).…”
Section: Introductionmentioning
confidence: 99%
“…A SDE é frequentemente considerada como reflexo de um sono não reparador, que pode ser causado por distúrbios do sono, bem como pode acarretar a elevação dos níveis de cortisol, responsável pelo agravamento de doenças como hipertensão e diabetes (TEIXEIRA, 2006;BIXLER et al, 2005;BAKSHI, 2003;OHAYON, 2008;STEPANSKI et al, 2002). Além de a SDE ser um importante sintoma dos distúrbios do sono, sua quantificação é um importante método diagnóstico subjetivo que pode discriminar pacientes com distúrbios do sono e indivíduos sem esses distúrbios (FORBES, 1997).…”
Section: Introductionunclassified
“…The need for prevention and effective treatment instrument has to be emphasized [16][17][18]. It has been shown that daily information and sensation sleep are indispensable [19][20][21], typical signs of sleeplessness are missed and diagnose might be therefore deferred in the pediatric medicine [22][23][24]. Sleeplessness and sleep disturbance influence child's behavior, otherwise behavioral disturbance can influence sleep customs [25][26][27].…”
Section: Introductionmentioning
confidence: 99%